Content analysis of barriers to delivering maternity care to women with physical disabilities: A qualitative study - Mehri Seiedzadeh; Mohammad Saeed Khanjani; Kianoush Abdi; Maryam Latifian (BMC Public Health)
Abstract Background Women with physical disabilities face many barriers in accessing safe, respectful and acceptable health care. This study was designed and conducted with the aim of identifying the barriers of delivering maternity care to women with physical disabilities. Methods This study was conducted with a qualitative research method of guided content analysis, and it explained the barriers to prenatal care in women with physical disabilities in Kermanshah province. In this study, a targeted sampling method with maximum diversity was used, and in order to collect data, face-to-face semi-structured interviews were used with open questions and, if necessary, follow-up and probing questions. A total of 24 people (12 pregnant women with physical disabilities and 12 antenatal care providers) participated in this study, and the data collection period lasted 10 to 12 months. In this study, the comparative analysis method was used, and Guba and Lincoln criteria were used for the accuracy and strength of the data. Results Barriers to providing care for pregnant women with disabilities in two themes, barriers related to stakeholders, including classes of society-related barriers, barriers related to healthcare providers, family-related barriers, barriers related to companions and barriers related to women with physical disabilities, and barriers related to support organizations, including classes: the lack of a systematic support system, the lack of a systematic care program and poor accessibility were categorized. Conclusions The findings of the present study showed that there are many obstacles in the field of providing care to women with disabilities, and knowing these factors will make the program managers and policy makers in the field of health and rehabilitation, with a closer look at the existing capacities of the country, to provide these cares to women with physical disabilities and their families should take more effective steps and adopt and implement the necessary mechanism in the field of policy making and planning in order to reach a better situation.